The Relationship of Motivation, Work Discipline and Leadership on Employee Performance - Ridwan, Muhammad; Mulyani, Sitti Rizki; Putra, Rio Andhika (UPI YPTK Journal of Business and Economics, 2024)
This study aims to determine the effect of the relationship between motivation, work discipline and leadership on employee performance at PT Bank Tabungan Negara (Persero) Padang Branch. The method used is multiple linear regression analysis by distributing questionnaires to 89 respondents. Hypothesis testing using T test and F test. The results of the study obtained based on the Persian Test (t Test) obtained: (a) there is a significant influence between the relationship between motivation and employee performance as evidenced by the t count value> t table (3.613> 1.988) with a significant level (0.001 <0.050), (b) there is a significant influence between the relationship between Work Discipline and employee performance as evidenced by the t count value> t table (2.713> 1.988) with a significant level (0.008 <0.050), (c) there is a significant influence between the relationship between Leadership and employee performance as evidenced by the t count value> table (2.627> 1.988) with a significant level (0.010 <0.050). Then based on the simultaneous hypothesis test (F Test) it can be seen that the f count value is 46.410 with a significant level (0.000 <0.050). So the writer concludes that the influence of motivation, work discipline and leadership on the performance of employees of Bank BTN Padang branch based on the Determination Coefficient (R Square) test, the value is 0.622 or 62.2%. This shows that the percentage contribution of the influence of motivation, work discipline and leadership variables on employee performance is 0.609 or 60.9%.